Physical characteristics and weight relationship of Gigantochloa scortechinii (Buluh Semantan) 1-,2- and 3-year old natural stand bamboos - Mohamed, Azmy; Othman, Sulaiman; Wahab, Razak; Hashim, Rokiah (Universiti Putra Malaysia Press, 2011)
Physical characteristics, such as average number of internodes, internode length, culm wall thickness, circumference of internodes, and weight of culm, branch and leaf of 1-, 2- and 3-year old culms were determined. Data were gathered from 47 to 62 of 1-, 2- and 3-year old culms in Kedah, Peninsular Malaysia. Significant linear relationships between weight and solid volume of the bamboo were observed for all the various ages studied. In addition, their corresponding regression equations were also determined. The 3-year old culm had the biggest mean for all the characteristic features, except for the Diameter-breast height (Dbh) and the culm wall thickness at the base. This was followed by the 2-year old culm. Meanwhile, regression of the height and culm weight on the Dbh gave the best regression line for 1 year old culm in terms of its r-squared value of 84 and 86 percent in comparison to the 2 and 3-year old culm.